REHABILITATION OF DEGRADED RANGELAND IN NORTHERN IRAQ - K.K. Kasim (Mesopotamia Journal of Agriculture)
This study was conducted at Mahalabia region in Ninevah province in Northern Iraq 45 km south west of Mosul city for the three successive seasons 99/2000, 2000/2001 and 2001/2002. The amount of the rainfall is less than 300 mm. This study included two field experiments. First, conducted on rangeland shallow highly gypsum soil (24% gypsum). The two sites were represented the rangeland in the cereal wheat belt area. In the first site, three treatments were established, first treatment was control represents (natural vegetation) and the two others were cultivated with vetch (Vicia sativa L. Var. IPA 2001) with and without triple superphosphate fertilizer 160 kg/ha. The second experiment was conducted on plate an shallow clay soil (52% clay). Also, three treatments were set up. First, was control represents (natural vegetation) and the two others were cultivated with annual medics (Medicago polymorpha Var. circle valley) with and without triple superphosphate fertilizer 160 kg/ha. The results revealed, that add phosphate reduced the phosphorus deficiency in the soil and lead to increase dry matter production for vetch and annual medics. Also, there was increase in the pod and seed yields, weight of 100 pods and 1000 seed of annual medics. On the contrary, phosphorus had no effect on the number of seeds/pod. There were significant differences in dry matter production between treatment cultivated by vetch and annual medics with and without phosphorus fertilizer in comparison with control treatment. Successful rehabilitation of degraded rangeland lead to increase the stability of animal wealth in the area and stop animal moving from place to another looking for natural vegetation for their feeding.